2000
DOI: 10.1074/jbc.m005701200
|View full text |Cite
|
Sign up to set email alerts
|

Müllerian Inhibiting Substance Inhibits Ovarian Cell Growth through an Rb-independent Mechanism

Abstract: Mü llerian inhibiting substance (MIS), a transforming growth factor-␤ family member, causes regression of the Mü llerian duct in male embryos. MIS overexpression in transgenic mice ablates the ovary, and MIS inhibits the growth of ovarian cancer cell lines in vitro, suggesting a key role for this hormone in postnatal development of the ovary. This report describes a mechanism for MISmediated growth inhibition in both a human epithelial ovarian cancer cell line and a cell line derived from normal ovarian surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
97
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 60 publications
4
97
1
Order By: Relevance
“…Regarding G1/S cell cycle regulation by MIS, we found that MIS did not induce most of the CDK inhibitors, but p19 INK4D and p21 Cip1 were slightly induced at 96 h. It is interesting to know that the transcript level of p16 INK4A was not changed by MIS in a previous study (19) and the same result was obtained from our analysis (Fig. 4B).…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Regarding G1/S cell cycle regulation by MIS, we found that MIS did not induce most of the CDK inhibitors, but p19 INK4D and p21 Cip1 were slightly induced at 96 h. It is interesting to know that the transcript level of p16 INK4A was not changed by MIS in a previous study (19) and the same result was obtained from our analysis (Fig. 4B).…”
Section: Discussionsupporting
confidence: 78%
“…These findings are significant since the MIS type II receptor has been detected in an increasing number of human gynecological tumors (35). In addition, it also suggests that MIS inhibits growth inhibition through the activation of p16, a negative cell cycle regulator (19), and consequently disrupts cell cycle progression and leads to apoptosis. In order to confirm the anti-neoplastic activity of MIS, we assessed the growth inhibition and apoptosis of MIS on OVCAR-8 cells, which was previously demonstrated to express MISRII and to respond to MIS by growth inhibition.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations